2019
DOI: 10.3389/fphar.2019.00777
|View full text |Cite
|
Sign up to set email alerts
|

Head-to-Head Comparison of the Hypoglycemic Efficacy and Safety Between Dipeptidyl Peptidase-4 Inhibitors and α-Glucosidase Inhibitors in Patients With Type 2 Diabetes Mellitus: A Meta-Analysis of Randomized Controlled Trials

Abstract: Background: The α-glucosidase inhibitors (AGIs) are commonly prescribed in Asian patients with type 2 diabetes mellitus (T2DM), but with a high incidence of gastrointestinal side effects. This study was aimed to compare the efficacy and safety of dipeptidyl peptidase-4 (DPP4) inhibitors and AGIs in T2DM patients in a meta-analysis. Methods: Randomized controlled trials were identified via systematic search of PubMed, Embase, and Cochrane’s Library datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
1
7
1
Order By: Relevance
“…Plenty of evidence has demonstrated that acarbose and DPP-4is at least have a weight-neutral effect (1,2,19,37). In consistence with the previous meta-analyses, acarbose was associated with a significant weight reduction compared with DPP-4is in our NMA (3,5). In accordance with previous studies, alogliptin probably had a greater weight reduction effect than linagliptin, sitagliptin, and vildagliptin (35,36).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Plenty of evidence has demonstrated that acarbose and DPP-4is at least have a weight-neutral effect (1,2,19,37). In consistence with the previous meta-analyses, acarbose was associated with a significant weight reduction compared with DPP-4is in our NMA (3,5). In accordance with previous studies, alogliptin probably had a greater weight reduction effect than linagliptin, sitagliptin, and vildagliptin (35,36).…”
Section: Discussionsupporting
confidence: 90%
“…Our NMA revealed that compared with placebo, acarbose and DPP-4is had significant hypoglycemic effects, since they both have a comparable glucose-lowering efficacy with their optimal doses. This result is quite different from our own and previous meta-analyses, suggesting that DPP-4is are superior to AGIs at glucose reduction (3,5,7). The reasons for the inconsistency may be as follows: Firstly, due to the limited source of pair-wise trials, one study, respectively, compared AGIs or DPP-4is with placebo, so the results may mislead the readers (7).…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…Newer oral medicines for patients with T2DM such as the DPP4 (dipeptidyl peptidase-4) and SGLT2 (sodium/glucose cotransporter 2) inhibitors have also been proposed (Naidoo et al, 2014;Imprialos et al, 2017;Bailey and Day, 2019;Li et al, 2019). However, there are major issues with affordability within public healthcare systems struggling to routinely make available metformin and basic insulins.…”
mentioning
confidence: 99%